Citizen-Centered Digital Governance: Institutional Determinants of Public Service Quality in Rural Indonesia - Eka Patmasari; Najeminur Najeminur; Herlina Herlina (Pattimura University, 2026)
This study examines the institutional determinants of public service quality within the implementation of citizen-centered digital governance in rural Indonesia. The study is motivated by the growing demand for public services that are efficient, transparent, responsive, and accessible through digital technologies, while rural local governments continue to experience institutional and organizational challenges in implementing digital transformation. A qualitative research approach was employed to explore how institutional capacity, administrative competence, digital technology utilization, transparency, and citizen participation shape public service quality. The research was conducted in Pammana District, Wajo Regency, South Sulawesi, Indonesia, involving twelve purposively selected informants representing government officials, frontline service providers, village representatives, and community members. Data were collected through semi-structured interviews, direct observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña consisting of data condensation, data display, and conclusion drawing. The findings indicate that institutional capacity serves as the foundation for successful digital governance implementation, while digital technology functions as an enabling mechanism for improving service efficiency and accessibility. Transparency enhances accountability by providing clearer information regarding public services, whereas citizen participation strengthens service responsiveness through continuous feedback and collaborative interactions. The study further reveals that organizational culture and human resource competence are essential in sustaining digital transformation beyond technological adoption. The novelty of this research lies in the development of an integrated conceptual framework demonstrating how institutional capacity, digital governance, transparency, citizen participation, and organizational adaptability collectively shape citizen-centered public service quality in rural governance contexts. The study recommends strengthening institutional capacity, expanding digital literacy initiatives, fostering adaptive organizational cultures, and promoting participatory governance to support sustainable digital transformation in rural public administration.